Traces of Islamic Architecture in the Design of the 'Gedung Sate' in Bandung - Rahadhian Prajudi Herwindo (Journal of Islamic Architecture, 2023)
Gedung Sate was built to accommodate various architectural styles derived from local and foreign elements. The local elements have been widely studied, such as those relating to the architecture of the 'Candi' on the island of Java. Many external elements are associated with the Moorish European style and that of the Dutch. However, according to the elements, it also indicates the existence of Indian Islamic architecture, the Mughal style. This study of the Islamic elements of Mughal India has not been pursued or presented any further. This study aims to identify the traces of Islamic architecture in the Gedung Sate, especially those derived from the Mughal, Moorish and local styles. This research method used a qualitative approach by studying the morphology of Gedung Sate and Mughal or Moorish buildings to identify the relationship between their architectural elements. The results show that Gedung Sate does indeed show the use of Mughal architectural elements, especially in the outer layout and mass, processing of the figure section, and the ornamental exterior column, while the Moorish influence is more visible in the processing of curved elements and column heads and slender interior columns showing light elements. The idea of using Islamic architecture is carried out to represent the splendor in the typology of new buildings in the prospective capital city of the Netherlands Indies, namely Bandung. Indian architecture is used as a reference because it is considered to have a close relationship with Candi as an important resource in Java.